New Approaches to the Technique of Improving the Technical and Tactical Fighters of the Kazakh-kures (Journal of Educational Sciences, 2017)
This article considers issues of improving the technical and tactical training of wrestlers kazakh-kures based on model characteristics. The article outlines options for improving technical and tactical actions, methodical techniques and Tasks with which you can solve the problems of each stage. Especial attention is paid to the characteristics of the sports activities of the fighter without consideration, which is difficult to tuck up effective methodical methods of influencing the preparedness of wrestlers. The authors took into account the records of stenographic records of competitive meetings. The effectiveness of the developed methodology is confirmed by the results of the pedagogical experiment. The model characteristics of the Kazakh-kures wrestlers developed by the author on technical and tactical training allow the coach to regulate in the training process a variety of protective and attacking actions, effectiveness of protection and attack, activity of performance of technical and tactical actions in competitive meetings.Key words: technical and tactical training, Kazakh-kures, training spells, competitive-based activity